If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -6 + x Solving 1 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 1 + -1x = -6 + 0 1 + -1x = -6 Add '-1' to each side of the equation. 1 + -1 + -1x = -6 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -6 + -1 -1x = -6 + -1 Combine like terms: -6 + -1 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 18x^2+x-35=0 | | 6x^2-27x=0 | | 30y=18y^2 | | 45=e+8 | | w^2+4w-96=0 | | 16x=103 | | 4h+6=2h+8 | | 3-7*(3+4x)=-18 | | 8x+7=43+2x | | -y^2+5y+6=0 | | 2n+13=29 | | 5x^2+32x+12=0 | | n^2+17n+72=0 | | 2q^2=8q | | 10b+8=32 | | Plotx=4 | | k^2-11k+30=0 | | d^2-5d=0 | | -2x^2-5x+8=0 | | 24x^2-7x=0 | | 125x^3-216=0 | | 3r+6=5r+12 | | 3m=-15 | | 6+h=-3 | | 4+5x=-x-8 | | 2n+3=-18 | | y-4(0)=0 | | x^3-3x^2-4x+12= | | -8+6(3x+5)=-25 | | 3x^2+14x=5 | | 5x=-4 | | -5(p+2)=(2p-15)+p |